Rechtliche Rahmenbedingungen von Serviceorientierten Architekturen mit Web Services - Nink, Judith (Universitätsverlag Göttingen, 2010)
Service-oriented architectures (SOA) with the interoperable software components Web Services employs a loose coupling between the participants. This provides economic and greater flexibility for companies. The young technology becomes more and more important, e.g. for companies organization and E-Commerce. Judith Nink writes about the legal requirements for SOAs used with Web Services. The dissertation is organized in three complexes, engaged with contracting questions, non-contracting liability and requirements for data protection in the scope of SOAs with Web Services.